Improved OER performance of an Anderson-supported cobalt coordination polymer by assembling with acetylene black. Issue 24 (8th June 2022) - Joshi, Arti; Sood, Parul; Gaur, Ashish; Rani, Deepika; Madaan, Venika; Singh, Monika
Abstract : First report on POM based hybrid i.e. Anderson cluster based solid for OER in a basic medium. Increased efficiency via assembly with acetylene black. The composite shows an overpotential of 330 mV to achieve a current density of 100 mA cm −2 with a stability of 40 h. Abstract : Anderson–Evans type polyoxometalates (POMs) are regarded as excellent nanosized inorganic building blocks for the construction of multifunctional hybrid materials because of their ease of covalent modification. A novel Anderson-based coordination polymer, [{Co(2-pzc)(H2 O)2 }2 H7 AlMo6 O24 ]·10(H2 O)·2.5(CH3 OH) (PS-13), has been synthesized and explored for electrocatalytic oxygen evolution. The integration with a co-catalyst, acetylene black (AB), results in AB&PS-13 (1 : 2), a composite material with substantial OER catalytic properties when compared to other known POM-based materials. It shows electrochemical oxygen evolution, with an overpotential of 330 mV at 10 mA cm −2, in alkaline aqueous solution (1 M KOH) with a stability of up to 40 h. As far as we are aware, this is the first report on electrocatalytic OER performance by any Anderson cluster based solid. Its integration with AB enhances the OER performance by approx. 11%. This research will offer a new perspective on the construction of efficient and resilient POM-based catalysts in the OER.